Banking in Central and Eastern Europe and Turkey: Challenges and opportunities - Christoph Klingen; Fabio Mucci; ç Iclem Erdem; Gunter Deuber; Stefan Kavan; Märten Ross (European Investment Bank (EIB), 2013)
This publication discusses the challenges and opportunities for the banking sectors in CEE countries and Turkey that arose after the financial crisis in 2007 and the on-going tensions on European sovereign debt markets. Its aim is to take stock of the views of commercial banks, the regulators and IFIs. It is also a useful reference text on banking in the region.
Keywords: 330